(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to map the patterns, trends, and thematic focuses of research on teachers’ self-efficacy using a bibliometric approach. A bibliometric method with keyword co-occurrence analysis was employed to identify the thematic structure and research development of teachers’ self-efficacy across educational levels. The data were obtained from scholarly publications indexed in Google Scholar and collected using the Publish or Perish software with the search string (“teacher self-efficacy” OR “teacher efficacy” OR “teaching self-efficacy”). The bibliographic metadata was exported in RIS format and analyzed using VOSviewer to generate density, network, and overlay visualizations. The findings indicate that teachers’ self-efficacy is a central concept dominating the research landscape and functions as a key connector among multiple research themes. The thematic mapping reveals several major clusters, including beliefs and teaching practices, collective teacher efficacy and school leadership, online learning and technology, teacher well-being, and the measurement of self-efficacy. Furthermore, the temporal analysis shows that topics related to online teaching, the COVID-19 context, and teacher well-being have emerged more prominently in recent years, reflecting the evolving challenges in contemporary education. This study contributes conceptually by providing a macro-level overview of the intellectual structure and developmental trends of research on teachers’ self-efficacy.